Educational principles for the teaching of vocabulary in Spanish as the language of instruction for immigrant students - Sanjuán Álvarez, Marta; del Moral Barrigüete, Cristina (Didáctica. Lengua y Literatura, 2019)
Understanding the nature of lexical competence should serve as a guide to focus teaching in a more systematic way. In this paper, general didactic principles are established, based on the various components that involve this competence, focused on a more effective teaching of the vocabulary of Spanish as a second language for immigrant students in the school context, according to their learning needs. The objective is to reinforce their lexical acquisition with clear objectives, content and methodological strategies, that include activities on comprehension, storage and recovery processes for the progressive use of academic vocabulary in Spanish. To conclude this paper, a didactic sequence of activities for the development of reading comprehension and lexical competence, aimed to immigrant students, is offered, based on a text from primary school textbook.